Development of Animated Video Learning Media to Improve the Cognitive Abilities of Early Childhood Children in Class A at TKIT Baitusshalihin Banda Aceh. - Karina Sukma; Fitriani Fitriani; Rahmat Fitra (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aimed to develop an animated video learning media that is valid, practical, and effective in improving the cognitive abilities of early childhood students in Group A1 at TKIT Baitusshalihin, Banda Aceh. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 children aged 4–5 years. Data were collected through observation, interviews, questionnaires, pretests, and posttests. The data were analyzed using qualitative and quantitative descriptive analysis, as well as the Shapiro–Wilk normality test and the Paired Sample t-Test with the assistance of IBM SPSS Statistics 26. The results showed that the animated video media achieved a very high level of validity, obtaining 100% from the media expert, 93.75% from the material expert, and 95% from the language expert. The practicality test result reached 100%, categorized as very practical. The effectiveness test demonstrated an increase in the average cognitive ability score of children from 31 in the pretest to 90 in the posttest. The normality test indicated that the data were normally distributed, with significance values of 0.550 for the pretest and 0.583 for the posttest. Furthermore, the Paired Sample t-Test yielded a significance value of 0.000 (< 0.05), indicating that the animated video media was effective in improving the cognitive abilities of early childhood children. Therefore, the developed animated video media is feasible to be used as an alternative learning medium to enhance early childhood cognitive development